Long-standing Temporomandibular Joint Dislocation in a Stroke Patient Reduced with Clamshell with Lock Orthopaedic Bone-holding Forceps - A Case Report - Taofeek Akin Akinniyi; Oji Okorie; Ethelbert Ikechukwu Ugwu; Adewale Francis Adejobi; Abimbola Jeremiah Adelabu; Olufemi Ogundipe (Annals of Maxillofacial Surgery, 2026)
Abstract Rationale: To restore oral function and facial aesthetics in a stroke patient with prolonged inability to close the jaws. Patient Concerns: A 50-year-old African female stroke survivor presented with a 9-month history of inability to achieve jaw closure, accompanied by persistent drooling, significant functional impairment and aesthetic concerns. Diagnosis: Chronic bilateral anterior temporomandibular joint (TMJ) dislocation. Treatment: Following failed manual reduction attempts, surgical reduction was performed under general anaesthesia. Bilateral sub-mandibular incisions allowed exposure of the mandibular angles. A clamshell bone reduction forceps with speed-lock was applied and used to deliver controlled traction, repositioning the condyles into the glenoid fossae. Outcomes: At 3 months, normal jaw closure, improved occlusion and restoration of oral competence were achieved, with residual anterior open bite. Take-away Lessons: Use of clamshell bone-holding/reduction forceps with a locking mechanism can be adopted in the reduction of chronic TMJ dislocation.